Damage Assessment of Two-Way RC Slab Subjected to Blast Load using Mode Approximation Approach - Huang, X.; Bao, H.; Hao, Y.; Hao, Hong (World Scientific Publishing Co. Pte. Ltd., 2016)
Significant research efforts have been invested on studying the response and damage of structures subjected to blast loads for better life and property protections. The single-degree-of-freedom (SDOF) approach has been widely adopted to simplify the structural response analysis for engineering design purpose. However, such an approach under certain circumstances oversimplifies the structural behavior and might not give reliable predictions of structural responses to blast loads. On the other hand, although detailed high fidelity finite element (FE) approach is able to give relatively accurate predictions of structural response, it is unfortunately not straightforward for application and very time-consuming, which impedes its application among engineers. Therefore, a method that can assure not only reliability but also efficiency is highly needed for design practice. In the present study, mode approximation method with Pressure–Impulse (P-I) diagrams is applied to analyze response and damage of RC slab due to blast load. Slab under analysis is assumed rigid-plastic and simply supported. Shear failure, bending failure and combined failure modes are considered based on different failure modes. Critical equations for structural shear and bending failures are derived respectively with appropriate failure criteria. P–I diagrams are then developed for quick damage assessments. The analytical results are verified by comparing with high fidelity numerical simulations. The reliability and efficiency of using this approach for design and analyzing RC slab response under blast loads are demonstrated.